PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN LAMPU LED PHILIPS (STUDI KASUS PADA WILAYAH KECAMATAN CIKARANG TIMUR) - Andari Ratna Widyastuti, Trie; Radhiya Salsabila, Kus (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to determine the effect of product quality and price on purchasing decisions. This study uses a quantitative approach. Data retrieval techniques with research instruments used are in the form of questionnaires and literature. Sampling technique in this study is Non- probability sampling the sample of this study is the Philips lamp users in the district of East Cikarang, Central Jakarta and obtained 150 respondents. Data analysis using multiple linear regression. In this study the authors used SPSS 26.The results of this study showed that the product quality (X1) there is a partial and significant influence on the purchase decision (Y) on Philips LED lamps by 72.7%. Price (X2) has a partial and significant influence on the purchase decision (Y) on Philips LED lamps by 66.1%. Other results, that together the product quality (X1) and price (X2) there is a significant influence on the purchase decision (Y) on Philips LED lights by 80.2% and the rest is influenced by other factors outside the model of this study that was not studied by the researcher